2011
DOI: 10.1002/ange.201105924
|View full text |Cite
|
Sign up to set email alerts
|

2,2′‐Biphospholes: Building Blocks for Tuning the HOMO–LUMO Gap of π‐Systems Using Covalent Bonding and Metal Coordination

Abstract: Organic p-conjugated systems are useful lightweight semiconducting materials for electronics. [1] The control of their HOMO-LUMO energy gap (E g ) is one of the key issues in the optimization of these materials for applications (organic light-emitting devices (OLEDs), organic field-effect transistors (OFETs), photovoltaic cells, etc.). [2] The E g of an isolated conjugated system (A; Figure 1) is a function of several structural factors including the bond-length alternation (E BLA ), aromatic character of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…For a first indication of whether it would be possible to perform selective chemistry on either of the two phosphorus heteroatoms, PPAs 5 a – c were subjected to oxidative conditions by using an excess amount of sulfur in CH 2 Cl 2 . Although such oxidation by sulfur is well established for phospholes[ 9 , 10d , h ] it has previously been shown that phosphaalkenes can also be oxidized by sulfur to thiaphosphiranes. [ 20 ] However, procedures for phosphaalkene oxidation usually suggest the addition of base to accelerate the reaction, although sulfurization is also described to proceed without a base but under extended reaction times.…”
Section: Resultsmentioning
confidence: 99%
“…For a first indication of whether it would be possible to perform selective chemistry on either of the two phosphorus heteroatoms, PPAs 5 a – c were subjected to oxidative conditions by using an excess amount of sulfur in CH 2 Cl 2 . Although such oxidation by sulfur is well established for phospholes[ 9 , 10d , h ] it has previously been shown that phosphaalkenes can also be oxidized by sulfur to thiaphosphiranes. [ 20 ] However, procedures for phosphaalkene oxidation usually suggest the addition of base to accelerate the reaction, although sulfurization is also described to proceed without a base but under extended reaction times.…”
Section: Resultsmentioning
confidence: 99%
“…[2] In principle, the capacity to change the properties of a phosphorus center actively during a process creates further important potential, such as on-off switching in catalysis, [3] or profound gating of the properties of electronic materials. [4] Studies of how phosphorus centers can be efficiently modulated using ferrocenes, [5] cobaltocenes, [6] TTF derivatives, [7] or other redox-active groups have appeared; however, these redox-active groups are often spatially close to the phosphorus center, so the electronic outcome of the redox change can be conflated with significant steric effects. This is obviously undesirable if geometrical properties need to be maintained, so the possibility of modulating the properties of a phosphorus atom by a molecular wire [8] is attractive.…”
mentioning
confidence: 99%
“…[18] It has recently been demonstrated that by altering the torsion angle of biphospholes the communication between the two phosphole rings can be tuned, and thus used to engineer the HOMO-LUMO gap. [19] Owing to the rigidity of the ethylene bridge between the two phosphole units in 4, p conjugation is well mediated and the lowest energy absorption maximum is observed at 445 nm (e = 7300 m À1 cm À1 ). The rigidity imposed by the ethylene spacer, as well as its contributions to the overall p system, gives rise to a 50 nm red shift compared to a 5,5'-diphenylsubstituted 2,2'-biphosphole.…”
mentioning
confidence: 99%